2015
DOI: 10.4238/2015.october.9.18
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association between the vitamin D receptor polymorphism rs2228570 and chronic periodontitis in a Han Chinese population

Abstract: ABSTRACT. The vitamin D receptor (VDR) is involved in the immune response and bone metabolism, both of which are implicated in the pathogenesis of chronic periodontitis (CP). In this study, we investigated the association between the VDR single nucleotide polymorphism rs2228570 and CP susceptibility in a Han Chinese population consisting of 440 moderate or severe CP patients and 324 controls. Genomic DNA was extracted from buccal epithelial cells and genotyped using matrix-assisted laser desorption/ ionization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
2
4
0
Order By: Relevance
“…Although previous studies have reported an association between the Fok I (rs2228570) variant and the risk of CP development in other populations, no significant differences were found among the groups in the population studied herein, which is in agreement with other findings in the literature . Moreover, the Cdx2 (rs11568820) variant was also not significantly associated with DM2 and CP in this population, which is in agreement with the findings in previous studies on periodontal disease …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Although previous studies have reported an association between the Fok I (rs2228570) variant and the risk of CP development in other populations, no significant differences were found among the groups in the population studied herein, which is in agreement with other findings in the literature . Moreover, the Cdx2 (rs11568820) variant was also not significantly associated with DM2 and CP in this population, which is in agreement with the findings in previous studies on periodontal disease …”
Section: Discussionsupporting
confidence: 92%
“…the FokI (rs2228570) variant and the risk of CP development in other populations, 25,26 no significant differences were found among the groups in the population studied herein, which is in agreement with other findings in the literature. 24,[40][41][42] Moreover, the Cdx2 (rs11568820) variant was also not significantly associated with DM2…”
Section: Although Previous Studies Have Reported An Association Betweenmentioning
confidence: 96%
“…On the contrary, Li et al (2008) reported that F allele increased the susceptibility of aggressive periodontitis in Chinese (Li et al, 2008) and Park, Nam, and Choi (2006) reported that CC genotype associated with increased risk for generalized aggressive periodontitis in Koreans (Park et al, 2006). However, several studies have also reported no association between rs2228570 and periodontis (Wang, Zhang, & Chen, 2015; Wang et al, 2009; El Jilani et al, 2015; Tachi et al, 2003). …”
Section: Discussionmentioning
confidence: 99%
“…11 Some of these genetic polymorphisms were previously studied in the dental caries aetiology context; [12][13][14][15][16][17] however, the results are contradictory. Following a similar pattern, studies evaluating periodontal disease [18][19][20][21][22][23][24][25] investigated the association between many genetic polymorphisms in VDR in the aetiology of periodontal diseases, including gingivitis. 15 Dental caries and gingivitis are common non-communicable diseases in children.…”
mentioning
confidence: 99%